Contributing factors to effective self-management in type 2 diabetes mellitus - Runtukahu, Audy Christian; Lestari Ismail, Dina Dewi Sartika; Yuliantun, Laily (Alma Ata University Press, 2025)
Background: Self-management plays a pivotal role in the management of Type 2 Diabetes Mellitus (T2DM). Active patient participation is crucial for achieving optimal glycemic control, preventing complications, and enhancing overall quality of life in the context of long-term, sustainable disease management.Objectives: This study aims to analyze the factors influencing self-management in patients with T2DM, to provide a foundation for developing more effective interventions that support patients in independently managing their condition.Methods: This study employed a literature review method by analyzing articles published within the last five years from the PubMed, ScienceDirect, and ProQuest databases. The search keywords used were “Self-management, Type 2 Diabetes Mellitus, and Factors influencing.” Out of 1,168 identified articles, 22 articles were selected based on relevant inclusion criteria, with a primary focus on self-management and its influencing factors in T2DM patients.Results: Self-management in patients with T2DM is influenced by both internal and external factors as well as individual skills. Key contributing factors include family support, cultural values, self-efficacy, emotional regulation, and time management. These elements interact dynamically, demonstrating that patients’ ability to manage diabetes is not determined by a single factor but rather by an integration of psychological readiness, supportive environments, and contextual influences. The findings highlight the importance of designing interventions that are holistic, culturally sensitive, and adaptable to patients’ daily realities. A holistic intervention approach, grounded in the bio-psycho-social and cultural model, is needed to enhance the effectiveness of self-management.Conclusions: Self-management is a crucial component in the management of T2DM. Ineffective implementation may lead to poor disease control and an increased risk of complications. Therefore, understanding the factors influencing self-management is essential for supporting sustainable and independent diabetes care.